Real-time SVD for the control of redundant robotic manipulators - Maciejewski, Anthony A., author; IEEE, publisher (Colorado State University. Libraries, 1989)
By taking advantage of the well-behaved nature of singular values and vectors, the computational expense of determining the SVD of the Jacobian matrix can be reduced to such an extent that on-line calculation becomes feasible. This permits more intelligent use of the extra degrees of freedom present with redundant manipulators, particularly with respect to the optimization of various secondary criteria, including obstacle avoidance, under the constraint of a specified end effector trajectory.
Keywords: matrix algebra; robots